Pengaruh Metode Digital Storytelling dalam Peningkatan Employee Engagement Karyawan PT PLN Jawa Barat - Marissa Febrianty Putri; Henndy Ginting; Missiliana Riasnugrahani (Universitas Kristen Maranatha, 2018)
This study is part of the thesis research and aims to see the effect of Digital Storytelling to improve employee engagement on employees of PT. State Electricity Company (PLN) Persero Distribution West Java (Disjabar). The design used in this research is Non-equivalent Control Group Design. The measuring tool used is a Gallup Q12 questionnaire created by Gallup (1996) consisting of 12 items that measure dependent variables. Test results validity of Gallup Q12 using alpha cronbach with value= 0,71. The results showed that there was a difference of employee engagement score in the experimental group of employees of PT. PLN Persero Disjabar before and after given digital storytelling intervention. From the research result, it is found that digital storytelling can increase employee engagement especially on dimension of Overall Satisfaction, What Do I Give? And What Do I Get?